FACTORS INFLUENCING EMPLOYEE TURNOVER INTENTION A CASE STUDY: PT SARI WARNA ASLI II BOYOLALI - Etsa Aulia Imama; Putut Haribowo; Luqman Khakim (JOBS (Jurnal Of Business Studies), 2016)
This research analyzes the influence of job stress, compensation and organizationalculture on employee turnover intention at PT Sari Warna Asli II Boyolali. This studyuses a multiple linear regression. The primary data that used in this research iscollected from questionnaire. The total of respondents in this research is 86 peoplewho are employees of PT Sari Warna Asli II Boyolali. The empirical result showedthat (1) the low level of job stress among employees have a significant positiveinfluence on employee turnover intention; (2) the high level of compensation andorganizational culture has a significant negative influence on employee turnoverintention; (3) the job stress is the factor that has the highest influence on employeeturnover intention. The result from SPSS 16 shows that from coefficient of adjusted Rsquared(R2) reveals that the independent variable (job stress - X1, compensation – X2and Organizational Culture – X3) influence on dependent variable (employee turnoverintention – Y) amount by 65,4%. Whereas, other factors, amount of 34,6%, are notmentioned in this research.